Citrus Leafminer, Phyllocnistis citrella Stainton (Insecta: Lepidoptera: Phyllocnistinae) - John B. Heppner; Thomas R. Fasulo (EDIS)
Revised! EENY-038, a 5-page illustrated fact sheet by J. B. Heppner and Thomas R. Fasulo, is part of the Featured Creatures collection. It describes this potentially serious pest of citrus that was discovered in Florida in 1993 — distribution, description, biology, host plants, damage, survey, and management. Includes references. Published by the UF Department of Entomology and Nematology, April 2010.